2015
DOI: 10.1108/sc-01-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Neighbouring behaviour, ethnic relations and informal control: a multigroup analysis

Abstract: Purpose – The purpose of this paper is to examine the validity of community organisation as part of the systemic model. Based on the systemic model of community crime, it is perceived that community networks are negatively correlated with victimisation. The authors consider an alternative interpretation, suggesting that these conceptual relationships can run opposite to the directions shown in the systemic model. The crime rate itself may change residents’ perception of neighbouring behaviour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Similarly, Steenbeek and Hipp (2011) found that high ethnic heterogeneity leads to increased disorder and decreased cohesion, which in turn affect the potential for social control. Likewise, empirical research in a Malaysian context found that residents from different cultures perceive social environment differently, given that perceived neighbouring behaviour, territorial attitudes and perceived risk vary across cultures (Hedayati et al, 2015). As the study was conducted in a homogenous neighbourhood, future research may bring new insights to the body of knowledge by focusing on homogenous and heterogeneous neighbourhoods.…”
Section: Recommendations For Future Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, Steenbeek and Hipp (2011) found that high ethnic heterogeneity leads to increased disorder and decreased cohesion, which in turn affect the potential for social control. Likewise, empirical research in a Malaysian context found that residents from different cultures perceive social environment differently, given that perceived neighbouring behaviour, territorial attitudes and perceived risk vary across cultures (Hedayati et al, 2015). As the study was conducted in a homogenous neighbourhood, future research may bring new insights to the body of knowledge by focusing on homogenous and heterogeneous neighbourhoods.…”
Section: Recommendations For Future Researchmentioning
confidence: 97%
“…Items were adapted based on the work of Greenberg et al (1982). Social cohesion items were adapted from the work of Hedayati et al (2015), Reynald (2011), andSampson et al (1997) on a seven-pint Likert scale (1=strongly disagree, 7=strongly agree). Items of perceived risk were adapted from Abdullah et al (2016), Franklin et al (2008) and Mason et al (2013) on a five-point Likert scale (1=very safe, 5=very unsafe).…”
Section: Survey Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this board game is to teach learners to become world citizens who can become engaged with an increasingly global world (Hedayati et. al.…”
Section: Racism -Save Tom!mentioning
confidence: 99%
“…The Malays are presumed the privileged race because their bumiputera (sons of the soil) status is protected by the constitution (Alatas, 2013). The race dominates under Malay hegemony causing gaps and segregations in Malaysia (Hedayati, Abdullah & Maghsoodi Tilaki, 2015). As a consequence of power and privilege, this ethnic group is perceived as lazy, incompetent, and complacent (Norraesah Mohammad, 2005;Mahathir, 1970) which might affect how masculinity is institutionalised among men of this racial group.…”
Section: Masculinity In Multicultural Malaysiamentioning
confidence: 99%